High-precision bus voltage control based on NLESO and TSMC predicted load current and grid voltage differential feedforward - Xie, Di; Wang, Liangliang; Zhang, Zhi; Wang, Shoumo; Kang, Longyun; Yao, Jigang (Frontiers in Energy Research, 2023)
Power battery test equipment is widely used to produce and test new energy vehicles and storage containers. To address the problem of DC bus voltage fluctuations that affect the accuracy of output voltage and current, a high-accuracy bus voltage control strategy is based on nonlinear extended state observation (NLESO) and terminal silding mode controller (TSMC) load current estimation. Simulation and experimental results show that the control strategy has a good suppression effect on the DC bus voltage fluctuation and can effectively improve the accuracy of the DC side output voltage and current. Grid voltage differential feedforward is adopted, which can achieve fast suppression of DC bus voltage fluctuations in power battery test equipment and meet the high precision output requirements of the system DC bus.